Analisis Yuridis Penerapan Pidana Maksimal terhadap Pelaku Pelecehan Seksual Anak di Bawah Umur - I Kadek Ari Putra; Kharisma Nanda Satwika; Kade Richa Mulyawati (Fakultas Hukum, Universitas Warmadewa, 2025)
Sexual violence against children is a serious human rights violation that continues to increase in Indonesia. This study aims to analyze legal protection for underage victims, evaluate the effectiveness of existing regulations (including the Criminal Code and Child Protection Law), and identify the complex factors that cause this crime. Using a normative juridical method with a literature review approach, the results of the study show that although the formal legal framework is adequate, its effective implementation is still hampered by weak enforcement, limited victim rehabilitation, and a lack of inter-agency coordination. Causal factors include victim vulnerability, family dysfunction, patriarchal culture, and weak law enforcement. The implications of these findings demand a comprehensive approach through strengthening protection, increasing the capacity of law enforcement officials, ensuring rehabilitation, and public education to tackle child sexual violence more effectively.